Uma proposta de viabilização da relação entre o financiador e o prestador de serviços ambientais através de oráculos blockchain - Barros, Anderson Marinho Pontes de (2023)
The need for greater transparency and reliability in the investment and resource management stages of environmental preservation projects motivates the adoption of technologies that allow the monitoring and application of these resources in a transparent and auditable way, and ensure that these resources are released and used by organizations and environmental service providers in a responsible and correct manner. This work proposes a solution using the concept of blockchain oracles, which enables the operationalization of the Standing Forest Coin (SFC), a digital asset that allows the decentralized collection of resources for initiatives that aim to protect the Brazilian Amazon ecosystem. With the adoption of machine learning and digital image processing, the solution presents the oracle as a structure that will guarantee credibility and security for the resources used in the projects. The proposal will be evaluated by a set of experiments, with the aim of analyzing whether the performance of the architecture defined for the blockchain oracle meets the demands required by the SFC in its objective of enabling the relationship between the financier and the provider of environmental services.